THE EFFECT OF CONCRETE COMPRESSIVE STRENGTH TESTING USING RUBBER SEED SUBSTITUTION AS A PARTIAL REPLACEMENT OF FINE AGGREGATE - MARLIANA PUTRI; SAHAT MARTUA SIHOMBING; GALI PRIBADI (CV KULTURA DIGITAL MEDIA, 2024)
The idea of environmental conservation has influenced the development of more environmentally friendly construction technologies, with the integration of natural materials such as rubber seed waste into construction materials. The construction industry faces challenges from production waste and material requirements that increase with population growth. Utilizing waste as an alternative material not only reduces pollution but also helps conserve non-renewable natural resources, such as replacing sand with rubber seeds in concrete mixes. The results of compressive strength testing on normal concrete at the age of 28 days reached 440 kN (f´c 24.91 Mpa), while variation 1 of 5% rubber seed waste reached 310 kN (f´c 17.55 Mpa), and variation 2 of 10% rubber seed waste reached 276 kN (f´c 15.63 Mpa). The compressive strength of concrete using rubber seed waste as a fine aggregate substitution with a 5% variation obtained an average compressive strength at the age of 7, 14, and 28 days of 8.72 MPa, 15.06 MPa and 17.55 Mpa. The compressive strength of concrete using rubber seed waste as a substitute for fine aggregate with a 10% variation obtained the average compressive strength at the age of 7, 14, and 28 days of 7.81 MPa, 12.63 MPa, and 15.63 Mpa. It does not meet the SNI 1974-2011 standard that the compressive strength of fc'25 concrete plan at the age of 7 days is 60% with a value of 15.06 MPa, the age of 14 days is 84% with a value of 21.06 MPa, the age of 28 days is 100% with a value of 24.91 MPa.